2012
DOI: 10.3109/10826084.2011.644844
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Inhalant (Whitener) Use Among Street Children in a South Indian City

Abstract: A cross-sectional study was conducted in the year 2008 among 174 children in observation homes in Hyderabad, India, to estimate the distribution of inhalant (whitener) use among this population. Data were collected using an instrument developed for this purpose. About 61% of the children were boys and their mean age was 12.2 years (range 5-18 years). Whitener use was found in 35% of the children along with concurrent use of other substances. Peer pressure was the commonest cause reported for initiating substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…[ 10 ] Research conducted in Hyderabad reported that substance use was found in 35% of the children. [ 11 ] Research conducted in Egypt reported that nearly 91% of street children were misusing products containing volatile substances. [ 12 ] Researchers from Colorado, USA reported that the rates of lifetime and recent substance use ranged from 66% to 90% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 10 ] Research conducted in Hyderabad reported that substance use was found in 35% of the children. [ 11 ] Research conducted in Egypt reported that nearly 91% of street children were misusing products containing volatile substances. [ 12 ] Researchers from Colorado, USA reported that the rates of lifetime and recent substance use ranged from 66% to 90% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study conducted among 174 children in observation homes in Hyderabad reported that about 61% of the children were boys and their mean age was 12.2 years (range 5-18 years). [ 11 ] Study conducted in Pokhra Nepal documented that majority (68.8%) of the street children were between 11 and 15 years of age, with male dominance (95.8%). [ 16 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[121314] Another study from Hyderabad described the profile and determinants of inhalant use among street children who were in observation homes. [15]…”
Section: Introductionmentioning
confidence: 99%
“…[3,8] Inhalant use among children has been seen to precede or act as a predictor for substance use later as they grow up. [9][10][11][12] Despite long standing awareness of the signifi cant morbidity and mortality associated with inhalant abuse, research and concrete data on its use and effects has been comparatively sparse in India. For these reasons, we took up this study to have a preliminary idea about the prevalence and associated factors of inhalant use among adolescents in our State.…”
Section: Introductionmentioning
confidence: 99%